Le capitalisme fondé sur la connaissance et le changement dans les stratégies des entreprises industrielles - Mytelka, Lynn (Études internationales, 1983)
This paper explores the changing nature of contemporary capital accumulation focusing in particular on the increasing importance of knowledge inputs in the production process. The growing knowledge-intensity of production reflected in the role of design, research and development, marketing, management and advertising in the growth strategy of the firm, has had numerous consequences for the nature of competition amongst firms and for the internationalization of production. As increased knowledge-intensity of production gave rise to ever more rapid technological change in industry, the need for greater flexibility in production and labour processes became acute, more so as the global economic crisis deepened and competition from newly industrializing countries rose.Automation and sub-contracting were important new strategies. So too was the segmentation and delocalization of production processes to cheap labour countries in the Third World and Eastern Europe. More recently, as the costs and risks involved in R&D escalated, large corporations have also begun to decentralize knowledge production itself by funding research and development activities outside the MNC, and by internationalizing knowledge production itself through the establishment of research laboratories abroad or the implementation of a System of world product mandates for selected manufacturing subsidiaries.